2020
DOI: 10.21776/ub.jpacr.2020.009.01.509
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanically Extraction Process of Gambier (Uncaria gambier Roxb.) from Limapuluh Kota, West Sumatera and Its Antioxidant activity

Abstract: The extraction process from leaves and twigs of gambier (Uncaria gambier Roxb)plant was conducted mechanically by using traditional hydraulic press, conventional screw press, and modified twin-screw press. The leaves and twigs of gambier plant was obtained from traditional farmer in Limapuluh Kota, West Sumatera, Indonesia. The water, ash and catechin contents of the gambier extracts were analyzed based on SNI 01-3391-2000 using spectrophotometry and thermogravimetry method. Antioxidant activity analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It has been reported that both robusta and arabica generally contain functional compounds in chlorogenic acid. This compound was also discovered by [34] to be present in coffee as an antioxidant, with robusta reported by [38] to contain higher content at 43. 63% than arabica, which has 36.18%.…”
Section: Introductionmentioning
confidence: 73%
“…It has been reported that both robusta and arabica generally contain functional compounds in chlorogenic acid. This compound was also discovered by [34] to be present in coffee as an antioxidant, with robusta reported by [38] to contain higher content at 43. 63% than arabica, which has 36.18%.…”
Section: Introductionmentioning
confidence: 73%
“…Rahmawati and Fernando [ 67 ] investigated the phenolic content and antioxidant activity of the ethyl acetate extract of dried gambir leaves using the maceration method. Phenolic content using the Folin–Ciocalteu method, obtained phenolic content of 172.62 mg GAE/mL at a temperature of 80 °C, with an antioxidant activity using the DPPH method of 28.34 ppm.…”
Section: Uncaria Gambir Roxb Usesmentioning
confidence: 99%
“…The gambir is an extraction product of the gambir plant (Uncaria gambir Roxb) from the Rubinace family, a potential catechin producer from Indonesia. Gambir contains many monomeric flavonoids, almost totally catechins, and a trace of epicatechin (Widiyarti et al 2020). Gambir catechin purification has been successfully carried out (Yeni et al 2014;Ferdinal 2014) through 2-stage extraction.…”
Section: Introductionmentioning
confidence: 99%